Romeo and Juliet : the 30-minute Shakespeare - Newlin, Nick (30-minute Shakespeare., 2010)
"This cutting of ROMEO AND JULIET is edited to four key scenes, starting with the lyrical prologue and the foreboding opening brawl, which is played out in slow motion to music. Also included are the timeless balcony scene; the harsh scolding of Juliet by her father; and the final moments at the tomb. The edition also includes an essay by editor Nick Newlin on how to produce a Shakespeare play with novice actors, and notes about the original production of this abridgement at the Folger Shakespeare Library's annual Student Shakespeare Festival."--Publisher